Peran Kiai Dalam Pemilukada Di Pamekasan 2008 - Siddiq, Akhmad (Jurnal Review Politik, 2012)
The social structure of Madurese society gives a high position to kyai for playing roles both politics  and religion, as well as social and culture fields. Roles they say “bhepa’ bhebu’ guruh ratoh.” These affirms that Madurese people should regard parent first, then teacher (kyai), and at last ruler (ratoh). Yet, practically, people give more affection, loyalty, devotion, and dedication for the kyai than to their parent. From this reality, this paper aims to elucidate the inter-connection between politics and religion, in the process of local election of Pamekasan 2008. It articulates how the kyai intensively participated in local election using both social and religious domains. The study showed that  the roles of the religion, social structure, and politics “communicate” each other.b